1999
DOI: 10.2116/analsci.15.1265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Solvent on the Extraction of Europium(III) with 4-Isopropyltropolone

Abstract: During the course of conducting a series of studies concerning the solvent extraction of several metal ions by 2-hydroxy-4-(1-methylethyl)-2,4,6-cycloheptatrien-1-one (4-isopropyltropolone; Hipt), it was found that dinuclear chelate complexes of several metal ions were extracted.1-3 Since only chloroform 1,2 or only toluene 3 was used as the solvent in those studies, the effects of the solvent on the extraction and formation of dinuclear chelate complexes of these metal ions were not investigated. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…We demonstrated superior synergistic effect on heavier Ln(III) with the co-use of 4isopropyltropolone (Hipt) and phen in toluene, 14 making this extraction system a promising candidate for superior separation of lanthanoids. Hipt alone extracts Ln(III) in the form as the polynuclear metal complexes, [16][17] which are disadvantageous to extraction separation of different lanthanoids because these lanthanoids are co-extracted via formation of heteropolynuclear complexes containing them. On the other hand, the presence of phen as a synergist inhibits the formation of such polynuclear complexes substantially but not completely by adduct complex formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated superior synergistic effect on heavier Ln(III) with the co-use of 4isopropyltropolone (Hipt) and phen in toluene, 14 making this extraction system a promising candidate for superior separation of lanthanoids. Hipt alone extracts Ln(III) in the form as the polynuclear metal complexes, [16][17] which are disadvantageous to extraction separation of different lanthanoids because these lanthanoids are co-extracted via formation of heteropolynuclear complexes containing them. On the other hand, the presence of phen as a synergist inhibits the formation of such polynuclear complexes substantially but not completely by adduct complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…14 In the present study, the synergistic extraction of Ln(III) with Hipt and phen was investigated in o-dichlorobenzene (DCB) that has higher dielectric constant than toluene and thus is promising as an extraction diluent to inhibit formation of polynuclear complexes. 17 As a result of equilibrium analysis of the extraction data, it is found that the Ln(III) species are extracted not as polynuclear complexes but as ion pair in the presence of ClO 4 into DCB phase. The separation factors between different lanthanoids in the present extraction system was also examined by the simultaneous extraction of all the Ln(III) ions except Pm(III).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation